2019
DOI: 10.1017/dmp.2019.96
|View full text |Cite
|
Sign up to set email alerts
|

Ready to Respond: A Survey of Interdisciplinary Health-Care Students and Administrators on Disaster Management Competencies

Abstract: Background:A sense of competency and confidence in disaster management is linked to response willingness and efficacy. This study assessed current health-care student disaster competency curricula and resultant confidence.Methods:A survey was sent to students and administrators in nurse practitioner (NP), master of public health (MPH), and medical/osteopathic schools (MD/DO), assessing curriculum coverage of 15 disaster management competencies (1-4, total 15-60), and confidence in performing 15 related behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Lessons learned from the pandemic reinforced the empirical evidence that nurses and other health care providers were not well prepared to respond. 18 , 19 National nursing workforce preparedness is a crucial component of prelicensure education and lifelong professional development, including ongoing practice (regular drills and exercises). Schools of nursing, challenged by regulatory requirements, a lack of faculty preparedness, and other pressures, had not allocated sufficient time in their curricula to ensure that nurses were knowledgeable in infection control and disease containment strategies, the selection and appropriate use of PPE, and the fundamental concepts of disaster and pandemic response.…”
Section: Academic Nursing In a Postpandemic Worldmentioning
confidence: 99%
“…Lessons learned from the pandemic reinforced the empirical evidence that nurses and other health care providers were not well prepared to respond. 18 , 19 National nursing workforce preparedness is a crucial component of prelicensure education and lifelong professional development, including ongoing practice (regular drills and exercises). Schools of nursing, challenged by regulatory requirements, a lack of faculty preparedness, and other pressures, had not allocated sufficient time in their curricula to ensure that nurses were knowledgeable in infection control and disease containment strategies, the selection and appropriate use of PPE, and the fundamental concepts of disaster and pandemic response.…”
Section: Academic Nursing In a Postpandemic Worldmentioning
confidence: 99%
“…The RITN concept of operations is based on the anticipated surge in distant communities following the large-scale release of radiation or the detonation of an improvised nuclear device 15 in which tens of thousands of patients will need to be cared for by specialists who have dealt with the complications resulting from hematopoietic transplantation that mimic the symptoms of acute radiation syndrome. 16 RITN collaborates with the US federal Department of Health and Human Services-Assistant Secretary for Preparedness and Response to coordinate the movement of patients through its National Disaster Medical System (NDMS).…”
Section: Discussionmentioning
confidence: 99%
“…Two unique RITN health-care workforce surveys were developed, 1 for MDs/APPs and 1 for RNs (Online Appendix A), based upon the specific scope of practice and the roles and responsibilities of each discipline. Each survey is a rapid self-administered questionnaire and survey questions were derived from previously published studies 12,14,15 addressing workforce development for radiation and nuclear events. The survey questions were reviewed for validity by subject matter experts at the Radiation Emergency Assistance Center Training Site (REAC/TS) in Oak Ridge, Tennessee.…”
Section: Survey Developmentmentioning
confidence: 99%
“…Preliminary studies of mapping capabilities related to disaster risks indicated there is considerable publicly available data on environmental hazards and natural disasters, but a lack of knowledge of the risks and necessary response by healthcare providers [ 32 , 33 , 34 ]. For example, Veenema et al [ 34 ] identified a full list of U.S. nuclear power sites, including nuclear power reactors and nuclear research and test reactors.…”
Section: Introductionmentioning
confidence: 99%